2015
DOI: 10.3109/08039488.2015.1025835
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled hospital admission in psychiatry: A systematic review

Abstract: Patient-controlled admission is a promising novel approach to inpatient care in psychiatry. However, available studies are small and quality of evidence is generally low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 23 publications
5
70
0
1
Order By: Relevance
“…Furthermore, some of the topics brought up by the informants may relate more to experiences of AN and AN treatment in general than to self‐admission specifically—e.g., problems associated with ambivalence and the ego‐syntonicity of symptoms in AN are certainly not unique to the self‐admission model. While previous studies have indicated that self‐admission can be a helpful treatment tool in psychiatry (Strand & von Hausswolff‐Juhlin, ), it is unclear for whom the model is most suitable and what factors that impact this viability. In, for example, patients with psychotic or affective disorders—groups that have previously been targeted in general psychiatric self‐admission programs—there may of course be within‐group differences regarding cognitive deficits, executive functions, insight etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some of the topics brought up by the informants may relate more to experiences of AN and AN treatment in general than to self‐admission specifically—e.g., problems associated with ambivalence and the ego‐syntonicity of symptoms in AN are certainly not unique to the self‐admission model. While previous studies have indicated that self‐admission can be a helpful treatment tool in psychiatry (Strand & von Hausswolff‐Juhlin, ), it is unclear for whom the model is most suitable and what factors that impact this viability. In, for example, patients with psychotic or affective disorders—groups that have previously been targeted in general psychiatric self‐admission programs—there may of course be within‐group differences regarding cognitive deficits, executive functions, insight etc.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, self‐admission to inpatient treatment for psychiatric patients has been in place for approximately 10 years, with promising results (Strand & von Hausswolff‐Juhlin, ). Self‐admission has led to increased patient participation and compliance, strengthened the patients’ abilities to handle their symptoms and their everyday life, and clearly reduced the total time spent in inpatient care.…”
Section: Introductionmentioning
confidence: 99%
“…One solution to increase the patient participation in mental health services is to make it possible for patients to self-refer to inpatient stay in mental health services. Several Community Mental Health Centers (CMHC) in Norway have implemented services called "self-referral to inpatient treatment" (SRIT) for patients with severe mental disorders (14)(15)(16). The aims of SRIT are to secure low threshold access to short term inpatient admissions and to increase patient participation and involvement in treatment choices and decisions (17).…”
Section: Introductionmentioning
confidence: 99%
“…The same group showed that this impairment was not present in the remitted summer state but only in depressive winter state (4). The recent study by Berman et al and the 2016 study by Laurenzo et al both included individuals with SAD, individuals with non-seasonal depression and healthy controls without depression (1,3). In these studies, the pupillary responses did not differentiate the two DOI: 10.1111/acps.12895…”
Section: Investigations Of Pupillary Responses In Depressionmentioning
confidence: 95%